2003
DOI: 10.1038/sj.ejcn.1601633
|View full text |Cite
|
Sign up to set email alerts
|

Cross-calibration of GE/Lunar pencil and fan-beam dual energy densitometers—bone mineral density and body composition studies

Abstract: Objective: In vitro and in vivo comparisons of bone mineral density (BMD) and body composition between GE/Lunar pencil (DPXL) and fan-beam (PRODIGY) absorptiometers. Design: Comparison of BMD, bone mineral content (BMC) and area of lumbar spine (L2-L4), femoral neck and total body. Total body composition compartments tissue (TBTissue), fat (TBF), lean tissue (TBLean) and %TBF were also compared. Setting: Centre for Bone and Body Composition Research, University of Leeds. Phantoms/subjects: A range of spine pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 30 publications
(23 reference statements)
5
54
1
Order By: Relevance
“…Elsewhere, and also using the more recent iDXA model, precision for TBL measurements have also been reported as excellent, with CVs of 0.4% (Rezzi et al, 2009), 0.52% (Faulkner et al, 2006) and 0.55% (Krueger et al, 2006).We also found excellent precision for the measurement of BMC, TBF and %TBF, compared with values reported elsewhere for older models of DXA and in a range of participants (Economos et al, 1997;Figueroa-Colon et al, 1998;Oldroyd et al, 2003). In this study, precision values for body composition parameters are comparable with those reported by studies elsewhere, which have also used the iDXA.…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…Elsewhere, and also using the more recent iDXA model, precision for TBL measurements have also been reported as excellent, with CVs of 0.4% (Rezzi et al, 2009), 0.52% (Faulkner et al, 2006) and 0.55% (Krueger et al, 2006).We also found excellent precision for the measurement of BMC, TBF and %TBF, compared with values reported elsewhere for older models of DXA and in a range of participants (Economos et al, 1997;Figueroa-Colon et al, 1998;Oldroyd et al, 2003). In this study, precision values for body composition parameters are comparable with those reported by studies elsewhere, which have also used the iDXA.…”
Section: Resultssupporting
confidence: 60%
“…There were large margins in CVs between machines for TFM (iDXA: 0.8%, Prodigy: 2.5%) and %TBF (iDXA: 0.9%, Prodigy: 2.7%). Although it should be considered that the participants measured in this study were generally larger in body size (BMI: 25.8 (5.1) vs 21.6 (4.4) kg/m 2 ) (Oldroyd et al, 2003), the results would imply superior reproducibility of the iDXA for the measurement of body composition.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous studies have evaluated relationships between DPX devises and the newer narrow fan bean densitometers (Prodigy). In general, small differences between the two types of absorptiometry were found, and by use of cross-calibration equations and factors, results from the two different devices were considered compatible [19,20].…”
Section: Discussionmentioning
confidence: 99%